ANALISA KAPASITAS KEBUTUHAN SISTEM ENERGI LISTRIK PLN DAN PANEL SURYA UNTUK PROSES PEMBUATAN GARAM - Rossoleh, Andriyan Herqi; Jamaaluddin, Jamaaluddin; Sulistiyowati, Indah; Ayuni, Shazana Dhiya (Jurnal Al Ulum LPPM Universitas Al Washliyah Medan, 2025)
This research discusses the utilisation of solar power plants (PLTS) in supporting salt production through a hybrid system with PLN electricity. The main objective is to design and optimise an efficient and sustainable renewable energy system, especially in remote areas with limited electricity supply and to determine the needs of PLN electricity and solar panel energy systems during the salt cooking process. This research method collects data by measuring various important components, such as the voltage from the inverter to the stove supplied from PLN electricity and solar panels to the battery. The test results show that salt production requires 700 watts of power from PLN for 1.5 hours with an average voltage of 195-196 volts and a current of 3.3-4 amperes. The voltage of the solar panel to the battery stabilised at 12.58 volts during sunny weather and decreased to 12.21 volts during cloudy weather. This research shows that the solar power plant for salt production has worked effectively. By building a hybrid system of PLN and solar panels to ensure the sustainability of salt production, especially in overcoming the instability of the power generated by solar panels due to weather changes